ConcepturealizeTM: A new contribution to generate real-needs-focussed, user-centred, lean business models - Graeme Joseph Allen (Journal of Innovation and Entrepreneurship, 2022)
It is widely accepted that somewhere in the region of 90-95% of startups fail. It is often suggested that the majority of unsuccessful startups either failed to identify a viable idea, or they failed to execute the idea effectively enough to get to market before running out of cash. Two approaches stand out as being particularly well-suited to addressing these problems: Design Thinking and Lean Startup, respectively. This paper presents the Concepturealize™ methodology that cross-applies Design Thinking and Lean Startup as a single iterative process and that enables the entrepreneur to generate real-needs-focussed, user-centred, lean business models. Existing literature reveals a need for further exploration of cross-application of Design Thinking and Lean Startup (and other related methodologies) in the areas of business model development and innovation. This work answers the research question by review of prior attempts to combine Design Thinking and Lean Startup and presenting the Concepturealize™ model that cross-applies Design Thinking and Lean Startup in a single iterative methodology and that enables the practitioner to generate real-needs-focussed, user-centred, lean business models. By following this new process model correctly, a practitioner will be guided to uncover a viable way to create value, develop a deep understanding of the value proposition, the target customers and how to reach and serve them, together with the expected revenue and costs, all needed to properly formulate the business model. Finally, the practitioner may use the Concepturealize™ model to retest the problem-solution fit and understand how the customers perception of value has altered, each time a new product or new features are launched, looking to continually add value at each cycle. Whilst prior research has explored how organisations may make use of both DT and LS, it has failed to demonstrate how they may be used in parallel, throughout the entire business model development process, instead it demonstrates examples of insight into where to transition from one model to the other. This work progresses the state of the art by following Design Science guidelines to present how the true, in-parallel, cross-application of DT and LS, in the context of business model development, is possible.
Keywords: 650; Business model design; Customer development; Design Thinking; Entrepreneurship; Innovation; Innovation management; Lean Startup; Value proposition